SOSIALISASI PENGEMBANGAN MODUL MATA KULIAH BERBASIS DIGITAL KEPADA MAHASISWA BARU - Aswar Aswar; Muhammad Anas; M. Amirullah; Akhmad Harum (As-Sidanah, 2023)
The need for digital-based teaching materials is crucial for students in today's new normal era, including in the religious approach guidance and counseling course. This condition is very prominent and is supported by the teaching lecturer evaluation (TLE) results, which show the low availability of teaching materials (library) for students. For this reason, this service is carried out to accommodate the needs of these students instead of being a form of actualization and responsibility of the author in carrying out the tri dharma of higher education. The service method used is participatory action research, with activity steps including; 1) Student Needs Analysis; 2) Preparation of Teaching Materials; 3) Making Guidance and Counseling E-Modules with a Religious Approach; 4) Dissemination of Guidance and Counseling E-Modules on a Religious Approach. The impact of dedication shows that: 1) Students need an introductory learning video and evaluative exercises on each material topic in the digital module; 2) The development of the E-Module received important input from the teaching team, guidance and counseling experts, and learning media experts as well as students during socialization; 3) Students respond positively to the presence of the Religious Approach Guidance and Counseling E-Module and are interested in programming and participating in these courses in the coming semester. Finally, this dedication has positive implications for the availability of digital-based teaching materials that can be used by guidance and counseling study program students.